#TITLE_ALTERNATIVE# - RUSMAN (NIM. 18012012), ADHITYA
Fuel cell is a new energy source power generator. Fuel cell produces 3 types of energy, which are electrical energy, water, and heat energy or waste heat. Fuel cell's waste heat can be used so that the power generation system became a cogeneration system, so that the efficiency rises. Absorption chiller is a chiller that uses heat energy as the power source, with single-effect absorption chiller water/lithium bromide as one type of absorption chiller. A fuel cell cogeneration system can be made by utilising the absorption chiller as the waste heat user. One type of consumer that can benefit from this cogeneration system is commercial buildings, one of them being hotel buildings. Based on the reasons above, the goal of this research is to analyse a fuel cell cogeneration system, with the focus being the absorption chiller system. The source of the data for the fuel cell system is taken from the research of the same system with the focus on the fuel cell system. Each fuel cell from the data source generated 40 kW of heat energy, which with system hotel load cases of 200 kW, 500 kW, and 1 MW, each case generated 160 kW, 400 kW, and 800 kW of heat energy. So that the heat energy can be used as best as possible, the research includes finding the optimum work area for the single-effect absorption chiller water/lithium bromide by simulation in ASPEN Plus. The decided optimum configuration generates a COP of 0.89. Based on the simulation using the decided optimum configuration, the cooling capacity of each case generated are 142 kW, 356 kW, and 712 kW, which for hotel buildings built at tropical countries, each case cools off 2333 m2, 5832 m2, and 11,667 m2 wide. The decided optimum configuration also increases the efficiency of the fuel cell cogeneration system into 64.78%.